Otherness in Pedagogical Theory and Practice: The Case of Roma (Alberta Journal of Educational Research, 2016)
This paper addresses the topic of the inclusion of Roma children in education in Europe through an examination of theory and practice in relation to the issues of Otherness and foreignness. Roma children entering school encounter a vastly different world from their home culture, with different expectations for teaching and learning, for relationships among learners, and with teachers. We address the question of whether the knowledge of these contradictions or discontinuities and knowledge of the ways in which any child from a minority group learns, is sufficient to address the issue of foreignness in educational contexts. The paper highlights the potential for interculturalism and intercultural pedagogies for engaging children from diverse cultures.Cet article porte sur la question de l’inclusion des enfants roms dans le système éducatif en Europe et ce, par un examen de la théorie et la pratique par rapport aux questions de l’altérité et l’extranéité. Les enfants roms qui rentrent à l’école sont confrontés à un monde bien différent de celui de leur propre culture, où les attentes face à l’enseignement et l’apprentissage ne sont pas les mêmes que celles qu’ils connaissent, ni les rapports des apprenants entre eux et entre les apprenants et les enseignants. Nous nous demandons si la conscience de ces contradictions ou discontinuités et la connaissance des façons dont apprennent les enfants de groupes minoritaires suffisent pour aborder la question de l’extranéité dans des milieux éducatifs. L’article souligne le potentiel de l’interculturalisme et des pédagogies interculturelles pour stimuler la participation des enfants de diverses cultures.